PENINGKATAN AREA JANGKUAN JARINGAN 4G LTE (STUDI KASUS KECAMATAN SAMARINDA ULU) - Maria Ulfah (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2018)
Improving the quality of the telecommunication network of 4G LTE technology must always be done considering the needs and the number of users (users) who have increased as well. In this research, optimization of coverage area (coverage area) in Samarinda Ulu District by using Atoll software. The design of the area scope uses 12 E Node B using 2 scenarios are Antenna 65deg 17dBi 0Tilt 1800MHz (Scenario 1) and Antenna 65deg 17dBi 2Tilt 1800MHz (Scenario 2). The total area for scenario 1 is 22,772 km2 while for the area for scenario 2 is 22,698 km2. . The difference of area between scenario 1 and scenario 2 is 0,074 km2 . Scenarios 1 and 2 can reach the Samarinda ulu subdistrict in densely populated sites.